Genetic control of leucocyte—endothelial cell interaction in collagen-induced arthritis. Issue 3 (11th March 2010) - Tu-Rapp, Hoang; Pu, Liying; Marques, Andreia; Kulisch, Christoph; Yu, Xinhua; Gierer, Philip; Ibrahim, Saleh M; Vollmar, Brigitte
Abstract : Objective: Despite considerable work on defining disease pathways, several aspects of collagen-induced arthritis (CIA) remain poorly defined, in particular those contributing to the initiation phase of the disease. It is thought that in CIA the activation of circulating leucocytes, their interaction with the endothelial lining followed by subsequent transendothelial migration and infiltration into tissue represents the first and determining step in a complex sequence of processes mediating tissue injury. In this study we attempted to define the genetic basis of this stage of disease using genetic linkage studies, in-vivo imaging and expression profiling. Methods: A genome scan with 132 informative markers was performed on 155 (DBA/1J×FVB/N) F2 mice. Linkage analysis was performed by combining genotyping data from the genome scan and the phenotypic data of leucocyte adherence, leucocyte rolling fraction, functional capillary density, centre line red blood cell velocity and capillary width as well as the expression level of the selected genes Cd44, Il13rα1, Ccr3, Defb3, Sele, Sell, Selp, Xcl1, Il1β, Tnfα and Ifnγ as traits. Results: Multiple classic quantitative trail loci (QTL) controlling leucocyte–endothelial cell interactions were identified on chromosomes 8 and 17 as well as expression QTL controlling the expression of several differentially expressed adhesion molecules and cytokines on chromosomes 1, 2, 5, 6, 7, 8, 12, 15, 16 and 17. Conclusion: The study describes for the first time QTL controlling the CIA initiating leucocyte–endothelial cell interaction.